Predicting enzymatic reactivity: from theory to design. (8th October 2013) - Świderek, Katarzyna; Tuñón, Iñaki; Moliner, Vicent
Abstract : Theoretical and computational tools can provide a detailed knowledge of the mode of action of enzymes. This knowledge can be systematized to be used as a guide for the design of new biocatalysts for industrial purposes. In this article, we illustrate the current view about the origin of enzymatic catalysis based on molecular simulations and its use in the design of new enzymes. Transition‐state stabilization in a preorganized active site seems to be the major source of catalysis, although some degree of protein flexibility is needed to reach the maximum catalytic efficiency. Development of a new enzyme must then consider the inclusion of TS stabilizing interactions either in a preexisting enzymatic structure (enzymatic redesign) or in a completely new designed enzyme ( de novo design). However, the lack of a detailed understanding of the link between sequence, structure, flexibility, and function still prevents the complete success of these strategies. WIREs Comput Mol Sci 2014, 4:407–421. This article is categorized under: Structure and Mechanism > Computational Biochemistry and Biophysics Electronic Structure Theory > Combined QM/MM Methods Molecular and Statistical Mechanics > Molecular Dynamics and Monte-Carlo Methods Abstract :